Malek Bennabi’s Discourse: A Critical Perspective - AIT BENALI, Ounissa (Journal of Science and Knowledge Horizons, 2025)
This article explores the political and cultural dimensions of Bennabi’s (1954) essay included in his book Vocation of Islam. It takes its bearings from the method of critical discourse analysis as proposed by Fairclough Norman (1995) in his book Critical Discourse Analysis: The Critical Study of Language. The study investigates three primary questions: first, the extent to which Bennabi’s ideas represent not only a pioneering historical perspective but also a visionary forecast of imminent changes in the postcolonial landscape. Second, it examines the pragmatic and cultural dimensions that Bennabi emphasized as foundational for an awakening and renaissance in the Muslim world. Finally, the study evaluates Bennabi’s provisional plan for enacting change, and fostering societal and cultural reform. By analysing these aspects,[i] the study aims to highlight Bennabi’s contributions to understanding and shaping the trajectory of postcolonial development in the Muslim world